A STUDY OF ANXIETY EXPERIENCED BY EFL STUDENTS IN PRESENTING PROPOSAL SEMINARS AT ENGLISH STUDY PROGRAM MUHAMMADIYAH UNIVERSITY OF BENGKULU - Sinarman Jaya; Nadila Oktavia (Teaching English and Language Learning English Journal, 2022)
This descriptive qualitative research aimed to find out the factors that cause anxiety in EFL students when presenting proposal seminars. A number of 20 students who had carried out proposal seminars participated as the subject of this research. Video and audio recording were conducted during the interviews to find out the factors of students’ anxiety during the presentation of the proposal seminars. The interviews revealed that, there were several factors that cause students’ anxiety in presenting proposal seminars, such as fear of failure, fear of negative criticism, lack of vocabulary, lack of grammar, poor pronunciation, fear of losing the thread of material, fear of being stopped, negative thinking, fear of making mistake, fear negative evaluation, and feel incompetent or appearing awkward in front of many people. It is suggested that EFL students who intend to conduct proposal seminars consider those factors to minimize anxiety. The finding of this research at the same time can be as a reference to create a better proposal seminar presentation. The last but not least, material mastery, presentation practices, watching some similar videos of seminars presentation, hard effort, and determination are truly essential factors contributing to the success of any proposal seminars presentation. Keywords: Anxiety, presentation, proposal seminar